ADVERTISING DAN DAYA TARIK WISATA TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN DI WISATA PAGUNG AGROWISATA KEDIRI - Roufik Jufitasari; Erwin Syahputra; Iing Sri Hardiningrum (Commodities, Journal of Economic and Business, 2023)
The focus of this research discusses the problems of the influence of advertising and tourist attractions on the decision to visit Pagung Agrowisata Kediri. The aim of this study is to analyze the influence of advertising and tourist attractions on tourists' visitation decisions, both partially and simultaneously. The population in this study consisted of visitors between February 2023 and March 2023, totaling 378 visitors. Using purposive sampling, a sample of 79 respondents was obtained. The data collection method used a survey with the main instrument being a questionnaire. The analysis technique used inferential statistics, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using t-tests and F-tests. The results of this study indicate that the advertising variable has a positive and significant effect on tourists' visitation decisions at Pagung Agrowisata Kediri, with a significant t-value of 0.000 < 0.05. The tourist attraction variable also has a positive and significant effect on tourists' visitation decisions at Pagung Agrowisata Kediri, with a significant t-value of 0.001 < 0.05. Simultaneously, advertising and tourist attraction variables have a positive and significant effect on tourists' visitation decisions at Pagung Agrowisata Kediri, with a significant F-value of 0.000 < 0.05. The results of this study are expected to serve as a foundation for further understanding the relationship between advertising strategies and tourist attractions with visitation decisions